Management of children and adolescents with chronic myeloid leukemia in chronic phase: International pediatric chronic myeloid leukemia expert panel recommendations - Millot, Frédéric; Ampatzidou, Mirella; Moulik, Nirmalya Roy; Tewari, Sanjay; Elhaddad, Alaa; Hammad, Mahmoud; Pichler, Herbert; Lion, Thomas; Tragiannidis, Athanasios; Shima, Haruko; An, Wenbin; Yang, Wenyu; et al. (Leukemia, 2025)
The treatment strategy for children and adolescents with chronic myeloid leukemia in the chronic phase (CML-CP) has evolved from allogeneic hematopoietic stem cell transplantation (HSCT) to tyrosine kinase inhibitors (TKIs). With the advent of next-generation TKIs and new targeted therapies in the CML field, an international pediatric CML expert panel provides recommendations based on the medical literature (including previous pediatric guidelines), national standards, and treatment principles used in adults with CML-CP. Recommendations include diagnosis of the disease and details on managing the initial steps of care of children and adolescents with newly diagnosed CML-CP, including complications such as leukostasis. The treatment recommendations are based on the initiation of therapy with a first- or second-generation TKI according to the allocated European Treatment and Outcome Study (EUTOS) long-term survival score risk group of the patient. The subsequent steps are based on the results of recommended monitoring which can justify a switch to another TKI or a drug in development if there is resistance or toxicity. The panel also provides recommendations regarding the discontinuation criteria for TKIs in children and adolescents in sustained deep molecular response. Allogeneic HSCT is not recommended as the first-line of treatment for children with CML-CP but is to be considered in case of progression to the advanced phase or failure of several lines of treatment. The present treatment and management recommendations are intended to provide advice to clinicians in view of optimizing the care and the outcome of children and adolescents with CML-CP.
Keywords: Hematopoietic Stem Cell Transplantation; Disease Management; inhibitory proteinkinas; transplantace hematopoetických kmenových buněk; Humans; chronická myeloidní leukemie; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Leukemia, Myeloid, Chronic-Phase; Protein Kinase Inhibitors; management nemoci; Adolescent; chronická fáze myeloidní leukemie; dítě; lidé; mladiství; Child